Intracellular Storage Reduces Stoichiometric Imbalances in Soil Microbial Biomass – A Theoretical Exploration - Manzoni, Stefano; Ding, Yang; Warren, Charles; Banfield, Callum C.; Dippold, Michaela A.; Mason-Jones, Kyle (Frontiers in Ecology and Evolution, 2021)
Microbial intracellular storage is key to defining microbial resource use strategies and could contribute to carbon (C) and nutrient cycling. However, little attention has been devoted to the role of intracellular storage in soil processes, in particular from a theoretical perspective. Here we fill this gap by integrating intracellular storage dynamics into a microbially-explicit soil C and nutrient cycling model. Two ecologically relevant modes of storage are considered: reserve storage, in which elements are routed to a storage compartment in proportion to their uptake rate, and surplus storage, in which elements in excess of microbial stoichiometric requirements are stored and limiting elements are remobilized from storage to fuel growth and microbial maintenance. Our aim is to explore with this model how these different storage modes affect the retention of C and nutrients in active microbial biomass under idealized conditions mimicking a substrate pulse experiment. As a case study, we describe C and phosphorus (P) dynamics using literature data to estimate model parameters. Both storage modes enhance the retention of elements in microbial biomass, but the surplus storage mode is more effective to selectively store or remobilize C and nutrients according to microbial needs. Enhancement of microbial growth by both storage modes is largest when the substrate C:nutrient ratio is high (causing nutrient limitation after substrate addition) and the amount of added substrate is large. Moreover, storage increases biomass nutrient retention and growth more effectively when resources are supplied in a few large pulses compared to several smaller pulses (mimicking a nearly constant supply), which suggests storage to be particularly relevant in highly dynamic soil microhabitats. Overall, our results indicate that storage dynamics are most important under conditions of strong stoichiometric imbalance and may be of high ecological relevance in soil environments experiencing large variations in C and nutrient supply.